"Turn on" room-temperature phosphorescent biosensors for detection of hyaluronic acid based on manganese-doped ZnS quantum dots. Issue 6 (12th January 2018) - Li, Dongxia; Qin, Jin; Lv, Jinzhi; Yang, Jiajia; Yan, Guiqin
Abstract : Fabricating PDAD–Mn–ZnS QDs nanohybrids as a facile room-temperature phosphorescent biosensor for detection of hyaluronic acid. Abstract : Biosensors based on excellent optical properties of quantum dots (QDs) nanohybrids are efficient for biological detection. In this work, a room-temperature phosphorescent (RTP) PDAD–Mn–ZnS QDs biosensor was constructed with poly(diallyldimethylammonium chloride) (PDAD) as the modifier of MPA-capped Mn–ZnS QDs, and used to detect hyaluronic acid (HA). The newly-added HA induced severe electrostatic interaction with PDAD–Mn–ZnS QDs, leading to the aggregation between PDAD–Mn–ZnS QDs and HA and thereby enhancing RTP. The enhancement of RTP was proportional to the HA concentrations within certain ranges. On this basis, a high-performance HA sensor was built and this sensor had a detection limit of 0.03 μg mL −1 and a detection range of 0.08–2.8 μg mL −1 . This proposed RTP sensor can avoid interferences from the background fluorescence or scattering light of the matrix that are encountered in spectrofluorometry. Thus, this biosensor is potentially suitable for detection of HA in real samples without complicated pretreatment.